Hubungan antara Karakteristik Petani dengan Motivasinya dalam Membudidayakan Tanaman Tebu (Kasus Kelompok Tani Dewi Ratih 1, Desa Maospati, Kecamatan Maospati, Kabupaten Magetan) - DIAN KURNIASIH; WAYAN SUDARTA; NYOMAN PARINING (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
Correlation Between Farmer Characteristic With Their Motivation In CultivateA Sugar Cane (In Case Of Dewi Ratih 1 Farmer Group At Maospati Village,Subdistrict Of Maospati, Magetan Regency) Sugar cane plant plays an important role in meeting the sugar consumtion needs ofsociety and industrial sector. In order to support the improvement of sugar cane plantproduction, the government should provide an input or direction that is needed bysugar cane farmers as a motivation for farmers to increase the production of sugarcane as a raw material for sugar. The characteristics of the farmers have become oneof important factors that affect the farmer motivation in cultivation of sugar caneplant in farmer’s group of Dewi Ratih 1, Maospati Village, Maospati Districts,Magetan Regency. Which is expected to be a reference for the government and thefarmers in determine the policies and development strategies in order to make sugarcane farming can improve revenue and the welfare of the farmers. The purpose ofthis research is to identify the characteristics of the farmer, motivation of the farmersin cultivating sugar cane plant and determine the correlation between the farmerscharacteristics and the farmer motivation in cultivating sugar cane plant in farmer’sgroup of Dewi Ratih 1, Maospati village, Maospati districts, Magetan regency. Thissampling by using simple random method. Data analysis method that is used isdescriptive analysis and spearman rank correlation coefficient test. The result ofdescriptive analysis shows that the farmers characteristics included in the lowcategory, while the farmer motivation in cultivation of sugar cane plant included inthe medium category. The result of spearman rank correlation analysis shows that thecharacteristics of the farmers who have a significant correlation with the motivationof the farmers is age, household income, vast of arable land, the number ofhousehold members, and farming experience.